A Review of Requirement Prioritization Techniques in Agile Software Development - Saher, Najia; Baharom, Fauziah; Romli, Rohaida (2018)
Prioritization is a crucial process in Requirement Change Management (RCM), as erroneous requirements prioritisation may increase the cost of development and lead to project failures. In Agile Software Development (ASD), requirement prioritization (RP) is difficult to maintain and requires more formal process.Changes in the priority list leads towards rework. Moreover, requirement prioritization in Agile is a difficult task due to its volatile nature. Ignorance of critical requirements during prioritization will result in numerous problems like poor quality of product and unsatisfied client. This paper presents a comprehensive review of RP by reviewing the strengths and weaknesses of existing RP techniques.This paper also provides information related to the current state-of-the-art on techniques and practices of RP and the research gaps in related works. These findings will contribute as inputs to construct a framework for selecting suitable RP techniques in ASD which can help software practitioners in choosing suitable prioritization techniques for handling continuous requirement change in ASD.